Implementing Green Chemistry Principles for Circular Economy Towards Sustainable Development Goals - Ziyang Guo (AIDIC Servizi S.r.l., 2021)
Sustainable development goals (SDGs) were proposed for harmonious development for future, this aim is highly consisted with the idea of circular economy (CE) which can be achieved by applying green chemistry principles (GCPs). In this work the relationship between GCPs and SDGs are discussed from the perspective of input selection and reduction, sustainable design and safety management. And it also indicated the benefits of CE which creates a kind of green business model. By integrating GCPs and SDGs, the specific applications of renewable resources towards sustainable development are introduced. Afterwards, it explores the utilization of bio-derived resources and energy in bamboo industry, pulping industry and carbon neutrality for CE. Finally, the challenges and perspectives are proposed in governance, industry and academic aspects.